A word from the Editorial Board - Choliy, V. (Advances in Astronomy and Space Physics, 2012)
This issue of Advances in Astronomy and Space Physics (AASP) represents the new-born "thick" scientific journal. Our aim is to be a broadcast platform for those young scientists who work in astronomy, astrophysics, space physics and related areas: from space geodynamics and astrobiology to cosmology and high-energy astrophysics and in any field one can understand as related to mentioned above.